2020
DOI: 10.3389/fpubh.2020.587125
|View full text |Cite
|
Sign up to set email alerts
|

The Family Health Scale: Reliability and Validity of a Short- and Long-Form

Abstract: Families strongly influence the health of communities and individuals across the life course, but no validated measure of family health exists. The absence of such a measure has limited the examination of family health trends and the intersection of family health with individual and community health. The purpose of this study was to examine the reliability and validity of the Family Health Scale (FHS), creating a multi-factor long-form and a uniform short-form. The primary sample included 1,050 adults recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 46 publications
(44 reference statements)
2
59
0
2
Order By: Relevance
“…SEM is a valuable analytic tool because it allows one to control for measurement error and to examine multiple pathways simultaneously. Given that prior research has shown that the four family health outcomes are correlated [3], examining multiple pathways simultaneously was important for this analysis so that we could assess all of family health together rather than separately. Confirmatory factor analysis (CFA) was conducted to establish the measurement model.…”
Section: Analytic Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…SEM is a valuable analytic tool because it allows one to control for measurement error and to examine multiple pathways simultaneously. Given that prior research has shown that the four family health outcomes are correlated [3], examining multiple pathways simultaneously was important for this analysis so that we could assess all of family health together rather than separately. Confirmatory factor analysis (CFA) was conducted to establish the measurement model.…”
Section: Analytic Methodsmentioning
confidence: 99%
“…family. This aspect of family health aligns most closely with traditional measures of family functioning [3]. Family healthy lifestyle comprises a family's collective healthy choices through regular physical activity, eating fruits and vegetables, following doctor's recommendations, and seeking health care services as needed.…”
mentioning
confidence: 85%
See 3 more Smart Citations